Implementation of mental health improvement programs in private offices: A case study analysis / Pritharshini Palanisamy - Pritharshini, Palanisamy (2021)
Mental Health has become an important aspect in Malaysia recently. There are many cases of workers experiencing mental health issues at workplace. The aim of this study is to improve mental health level and quality of life for people affected by these issues. By providing healthy environment, work culture and appropriate processes to prevent mental health issues from occurring has become very important. In this study a private and government offices are selected to evaluate the level of mental issues occurrence, the reasons for the occurrence and the effect on work performance, health, and other factors. This study was conducted through survey and interview session. SPSS software was used to analyze the data from the survey question. Subsequently, recommendations are made to mitigate the mental health issues in this case. By using the DASS-21 (Depression, Anxiety and Stress Scale Assessment), it is found that 21% of the respondents experiencing mild depression, stress, and anxiety due to their workplace situations, where 12% were female and 9% were male. Aside from that, the survey results suggest that some of their companies do not value mental health as highly as productivity, and that their management is uninterested in resolving their employees' mental health difficulties. On the other hand, the hypothesis testing that were conducted shows that mental health and employers have relationship as the null hypothesis was accepted and alpha value is more than 0.05. From this study, a checklist of mental health interventions was proposed where employers can implement at their workplace to take care of their employees’ mental health continuously and mental health programs was proposed.